KORELASI DAMPAK PENCEMARAN LINGKUNGAN TERHADAP KEJADIAN STUNTING DI DUNIA - Yessy Aprihatin; Erpita Yanti; Putri Minas Sari; Milya Novera; Debby Sinthania; Anggra Trisna Ajani; Mariza Elvira (Jurnal Kesehatan Medika Saintika, 2025)
Various water quality pollutions have had a negative impact on children's health. One of the pollution that commonly occurs in urban and rural environments is the use of pesticides in agricultural environments. Pesticides are made for the specific purpose of causing harm (to insects, rodents, and other pests), they have the potential to cause serious damage to a developing fetus. Another cause that causes the environmental quality to decline, especially the air environment, is the bad behavior of the community in consuming cigarettes. This research method uses descriptive techniques, which describes how Environmental quality affects public health, especially in the impact of stunting among children under five. Environmental quality and community behavior will determine the health status of the community. Furthermore, a person's health status will affect the quality of life and productivity which in turn will affect their welfare. The existence of environmental pollution from various toxic chemicals such as excessive use of pesticides in the environment results in disturbances in infant growth and in early childhood. In addition, an increase in cigarette consumption of about two percent has been replaced by a decrease in expenditure on rice, protein and fat sources, as well as education. Household expenditure on meat and fish decreased by around 2.3 percent during 2012-2023. Yet, as many studies have shown, this type of expenditure will profoundly influence the future development of children in terms of weight, height and cognitive abilities.